A chemiluminescence immunoassay for precise automatic quality control of glycoprotein in human rabies vaccine. Issue 51 (17th December 2021) - Ye, Ke; Shi, Dawei; Zhang, Zhigao; Bian, Lun; Li, Zhaoyue; Liu, Tiancai; He, Chunhui; Xu, Sihong; Wu, Yingsong; Lin, Guanfeng
Highlights: First developing a fully-automated micromagnetic particles (MMPs) based chemiluminescence immunoassay platform which detects rabies virus glycoprotein. A suitable tool with better analysis perfomance and higher efficiency which is potential to be adopted by vaccine manufacturers to apply in vaccine quality control of multiple production steps. Abstract: Currently, quality control of glycoprotein in the human rabies vaccine is based on enzyme-linked immunosorbent assay (ELISA). However, ELISA does not match the needs of a modernised quality control system. For a long time, human rabies virus vaccine manufacturers have been devoted to seeking a detection platform that is sensitive, accurate, automatic, and feasible for practical applications. Therefore, our team invested major efforts into establishing a fully automated micromagnetic particle (MMP)-based chemiluminescence immunoassay (CLIA) platform. For vaccine quality control, MMP-coupled rabies virus glycoprotein monoclonal antibodies (S037) were used to capture the rabies virus. Another rabies virus glycoprotein antibody (S053) labelled with acridinium ester was added as a signal tracer. After pretreating the vaccine sample, the entire analysis was performed using a fully automated machine, which had a limited detection time (only 30 min) and eliminated manual error. Multiple experiments have identified the optimal conditions allowing valid and reliable assessment of vaccine potency. The CLIA platform has exhibited merits in terms of speed, robustness, high sensitivity (with a minimum detection value of 0.45 mIU/mL), considerable accuracy, and a wide linear range of detection (9.4–1200 mIU/mL). Furthermore, the results showed that the CLIA platform is consistent with the National Institutes of Health test and time-resolved fluorescent immunoassay (TRFIA) in quantitative analysis, and had a better analytic performance than TRFIA. Therefore, the CLIA platform presented here may be important for application in modern vaccine quality control.